(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Celiac disease (CD) is an autoimmune disorder of the small intestine related to gluten. CD is diagnosed by the evaluation of histologic findings according to the Marsh classification. Objectives: To evaluate the clinical and laboratory differences of CD according to Marsh classification. Patients and method: The records of ?Marsh 2 histologically diagnosed 132 cases were evaluated. Results: It was determined that 7(5.3%) cases were Marsh 2, 32(24.2%) were Marsh 3a, 73(55.3%) were Marsh 3b, and 20(15.1%) were Marsh 3c. Vomiting in Marsh 2 was significantly lower than Marsh 3b and Marsh 3c (respectively, 14.3% vs. 56.9%, p=0.029; and 14.3% vs. 75%, p=0.005). Hemoglobin was significantly higher in Marsh 2 than Marsh 3b and Marsh 3c (respectively, 11.9±1.7 vs. 10.5±1.6 g/dl, p=0.038 and; 11.9±1.7 vs. 9.8±1.6 g/dl, p=0.005). Positive detection ratio for tTG IgA was significantly lower in Marsh 2 than Marsh 3a, Marsh 3b and Marsh 3c (respectively, 66.7% vs. 100%, p<0.001; 66.7% vs. 100%, p<0.001; and 66.7% vs. 94.1%, p=0.003). After the onset of gluten free diet, the time passed for the disappearance of tTG IgA seropositivity is significantly shorter in Marsh 2 than Marsh 3c (6±3.6 vs. 9.7±2.5 months, p=0.017). Conclusions: Gastrointestinal symptoms are more frequent in patients with severe small intestinal mucosal injury. tTG IgA seropositivity is associated with more severe disease. Clinical and laboratory findings of the patients are exacerbated when histopathological findings improve in CD. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.259-265